Attitudes of the non-Catholic population in Northern Ireland towards the Irish language in Ireland - Merike Darmody (The Economic and Social Research Institute (ESRI), 2016)
Once holding a prominent position on the island, social, economic and political factors throughout the centuries have resulted in decline of the Irish language. The current situation of the Irish language on the island differs markedly between the Republic of Ireland and Northern Ireland. While historically the Irish language was used also by the representatives of other religions, over time it became strongly associated with Catholic identity. This paper explores the attitudes towards the use of the Irish language of adult non-Catholic population in Northern Ireland. It explores the link between language and national and religious identities, and seeks to identify factors associated with positive attitude towards the Irish language. The paper draws on 2013 Language Survey.
Keywords: 330; attitudes to the Irish language; fluency in Irish; future of the Irish language; national identity; religious identity